1997
DOI: 10.1080/016502597384668
|View full text |Cite
|
Sign up to set email alerts
|

Personality Development between 1 and 8 Years of Age in Swedish Children with Varying Child Care Experiences

Abstract: In this longitudinal study, 122 Swedish children were followed from an initial assessment at 16 months until they were 8.5 years of age. Parental ratings of field independence, ego-resilience, and ego-control were obtained using the California Child Q-set when the children averaged 28, 40, 80, and 101 months of age. These assessments of personality were then examined in the context of contrasting child care experiences. There was virtually no difference between the developmental trajectories of the children in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…In contrast, others have shown no effects of nonmaternal care experiences in the first 3 years on children’s peer interactions and personality development in early and middle childhood (Lamb, Hwang, Broberg, & Bookstein, 1988; Lamb et al., 1988; Wessels, Lamb, Hwang, & Broberg, 1997) or have shown that the earlier children entered nonmaternal care (Andersson, 1989; Rubenstein et al., 1981) or the more hours they spent in nonmaternal care in the 1st year (Field, Masi, Goldstein, Perry, & Parl, 1988), the better they scored on some measures of socioemotional and cognitive functioning. Again, effect sizes tended to be moderate to large in magnitude and sample sizes tended to be small.…”
Section: Nonmaternal Care In the First 3 Years: Effects On Children’smentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, others have shown no effects of nonmaternal care experiences in the first 3 years on children’s peer interactions and personality development in early and middle childhood (Lamb, Hwang, Broberg, & Bookstein, 1988; Lamb et al., 1988; Wessels, Lamb, Hwang, & Broberg, 1997) or have shown that the earlier children entered nonmaternal care (Andersson, 1989; Rubenstein et al., 1981) or the more hours they spent in nonmaternal care in the 1st year (Field, Masi, Goldstein, Perry, & Parl, 1988), the better they scored on some measures of socioemotional and cognitive functioning. Again, effect sizes tended to be moderate to large in magnitude and sample sizes tended to be small.…”
Section: Nonmaternal Care In the First 3 Years: Effects On Children’smentioning
confidence: 98%
“…Type of nonmaternal care. There is some evidence that the more time children spend in center‐based care relative to parental care (Loeb, Bridges, Bassok, Fuller, & Rumberger, 2007) or relative to any other kind of care (Belsky, 2001; Belsky et al., 2007), the more externalizing problems they have, though not all studies have identified this pattern (Hausfather et al., 1997; Wessels et al., 1997). A few studies have shown that type of nonmaternal care interacts with age of entry into nonmaternal care, but again, findings are inconsistent.…”
mentioning
confidence: 99%
“…In international comparisons Swedish day care appears to be of generally high quality due to factors such as teacher education, educational programs, localities, and equipment (Hwang & Broberg, 1992). Previous studies of non‐parental care in Sweden have shown either no differences between home‐reared children and children in non‐parental care or positive effects of such care regarding socio‐emotional development (Andersson, 1992; Wessels, Lamb, Hwang & Broberg, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…The CCQ serves this function well as a great deal of research has confirmed the reliability and validity of this tool (e.g., Block, Block, & Morrison, 1981; Caspi et al., 1992; Dollinger, 1992; John, Caspi, Robins, Moffitt, & Stouthamer‐Loeber, 1994; Parker & Stumpf, 1998; Weir & Gjerde, 2002). Furthermore, this instrument has commonly been used with mothers as a way to assess child personality (e.g., Caspi et al., 1992; John et al., 1994; Wessels, Lamb, Hwang, & Broberg, 1997; van Aken & van Lieshout, 1991; van Lieshout, De Meyer, Curfs, & Fryns, 1998).…”
mentioning
confidence: 99%